Overexpression of Thiamin Biosynthesis Genes in Rice Increases Leaf and Unpolished Grain Thiamin Content But Not Resistance to Xanthomonas oryzae pv. oryzae - Dong, Wei; Thomas, Nicholas; Ronald, Pamela C.; Goyer, Aymeric (Frontiers in Plant Science, 2016)
Thiamin diphosphate (ThDP), also known as vitamin B1, serves as an enzymatic cofactor in glucose metabolism, the Krebs cycle, and branched-chain amino acid biosynthesis in all living organisms. Unlike plants and microorganisms, humans are not able to synthesize ThDP de novo and must obtain it from their diet. Staple crops such as rice are poor sources of thiamin. Hence, populations that mainly consume rice commonly suffer thiamin deficiency. In addition to thiamin’s nutritional function, studies in rice have shown that some thiamin biosynthesis genes are involved in resistance to Xanthomonas oryzae (Xoo), which causes a serious disease in rice fields. This study shows that overexpression of two thiamin biosynthesis genes, 4-methyl-5-β-hydroxyethylthiazole phosphate synthase and 4-amino-2-methyl-5-hydroxymethylpyrimidine phosphate synthase involved in the first steps of the thiazole and pyrimidine synthesis branches, respectively, increased thiamin content up to five-fold in unpolished seeds that retain the bran. However, thiamin levels in polished seeds with removed bran were similar to those found in polished control seeds. Plants with higher accumulation of thiamin did not show enhanced resistance to Xoo. These results indicate that stacking of two traits can enhance thiamin accumulation in rice unpolished grain. We discuss potential roadblocks that prevent thiamin accumulation in the endosperm.